Stimulants for the Control of Hedonic Appetite - Poulton, Alison S.; Hibbert, Emily J.; Champion, Bernard L.; Nanan, Ralph K. H. (Frontiers in Pharmacology, 2016)
The focus of this paper is treatment of obesity in relation to the management of hedonic appetite. Obesity is a complex condition which may be potentiated by excessive reward seeking in combination with executive functioning deficits that impair cognitive control of behaviour. Stimulant medications address both reward deficiency and enhance motivation, as well as suppressing appetite. They have long been recognised to be effective for treating obesity. However, stimulants can be abused for their euphoric effect. They induce euphoria via the same neural pathway that underlies their therapeutic effect in obesity. For this reason they have generally not been endorsed for use in obesity. Among the stimulants, only phentermine (either alone or in combination with topiramate) and bupropion (which has stimulant-like properties and is used in combination with naltrexone), are approved by the United States Food and Drug Administration (FDA) for obesity, although dexamphetamine and methylpenidate are approved and widely used for treating attention deficit hyperactivity disorder (ADHD) in adults and children. Experience gained over many years in the treatment of ADHD demonstrates that with careful dose titration, stimulants can be used safely. In obesity, improvement in mood and executive functioning could assist with the lifestyle changes necessary for weight control, acting synergistically with appetite suppression. The obesity crisis has reached the stage that strong consideration should be given to adequate utilisation of this effective and inexpensive class of drug.